Impact of High and Growing Public Debt on Economic Growth in SAARC Countries: An Econometric Analysis - Muhammad Reehan Hameed; Muhammad Abdul Quddus (Journal of Political Studies, 2020)
Developing countries of South Asia are continuously facing problems in managing and servicing their huge public debt obligations. This high level of public indebtedness has serious implications on countries economic development. However, their economic performance continues to deteriorate due to significant outflow of resources to meet their debt obligations. The study designs to examine the structure of public debt its implications on economic growth in of SAARC economies of Bangladesh, India, Pakistan and Sri Lanka. For this purpose the penal data of selected countries for the period of 1990-2018 has been used. From the literature several factors through which public indebtedness effect economic growth have been identified: public debt to GDP ratio, debt servicing as a ratio of export earnings, net foreign financing as a ratio of total deficits, private and public investment as ratio of GDP. Besides these variables some policy, fundamental and shock variables like inflation, exchange rate, terms of trade and population growth. For analysis of data the econometrics techniques like Fixed Effect Model, Hausman Test and PMG/ Panel ARDL approach have been applied to analyze the long run association among the regressors. The results of the study reveal that public debt negatively affected the economic performance both in short period and long period. The study concludes that presently, simultaneous achievement of desirable level of economic growth and public debt stock seems to be difficult and could remain elusive if some serious measures are not taken.